Corrigendum - Biazar E (Dove Medical Press, 2011)
Biazar E, Heidari M, Asefnezhad A, Montazeri N. The relationship between cellular adhesion and surface roughness in polystyrene modified by microwave plasma radiation. International Journal of Nanomedicine. 2011;6:631-639.The correct spelling of the third author's name is "Asefnejad."Original article